GEOMETRI DAN FRAGMENTASI BATUAN MENGGUNAKAN METODE KUZ-RAM DI PT SEMEN BOSOWA MAROS PROVINSI SULAWESI SELATAN - Soesiadhy Palimbu; Yulius G. Pangkung (INTAN Jurnal Penelitian Tambang, 2021)
Fragmentation of blasted rock aims to determine the average size and size distribution of blasted fragmentation. In fragmentation analysis, blasting geometry calculates to acquire the burden, spacing, stemming, and sub drilling values. The primary data needed in rock fragmentation resulting from blasting are rock mass weighting data, explosive data, and actual blasting data obtained from previous researchers. The results of the actual fragmentation analysis obtained are the actual average fragmentation size of 21,83 cm and the average size of fragmentation using the ICI-Explosives design of 27,22 cm. The actual fragmentation size distribution is 1,92 % 100 cm and 99,08 % 100 cm. Meanwhile, the results of the size distribution of the fragmentation resulting from blasting using the Kuz Ram method using the ICI – Explosives blasting geometry design will produce fragmentation sizes of 0,84 % 100 cm and 99,16% 100 cm.